Principles and practice of constraint programming : 25th International Conference, CP 2019, Stamford, CT, USA, September 30-October 4, 2019, Proceedings /: 25th International Conference, CP 2019, Stamford, CT, USA, September 30-October 4, 2019, Proceedings. (2019) - Unknown
No abstract available